Gambaran Pengetahuan Tentang Prebiotik Jahe Untuk Penurunan Nyeri Haid Pada Mahasiswi DIII Kebidanan Universitas Ngudi Waluyo Ungaran Tahun 2021 - Atika Purnama Sari; Rini Susanti (Journal of Holistics and Health Science, 2021)
According to WHO, in the world the incidence rate is quite high. The incidence of dysmenorrhoea in young women on average: 16.8% -81%. The average in European countries menstrual pain occurs in women 45-97%. The lowest Bulgarian prevalence is 8.8%, the highest is 94% in Finland. The highest prevalence of dysmenorrhea is often found in adolescent girls, which is estimated: 20-90%. About 15% of adolescents have severe dysmenorrhea (Sulistyorinin, 2017). The purpose of this study was to determine the knowledge of students about ginger prebiotics to reduce menstrual pain in students of DIII Midwifery, Ngudi Waluyo Ungaran University in 2021.Quantitative descriptive research with survey. The sample in this study were 32 female students of DIII midwifery, Ngudi Waluyo Ungaran University. Sampling technique with sampling Total. Data analysis using frequency distribution. The results of this study are then given an interpretation based on the variables studied based on the criteria of good, adequate and insufficient. The results of this study indicate that students of DIII midwifery at Ngudi Waluyo Ungaran University have knowledge of Ginger Prebiotics for Menstrual Pain Reduction, the overall knowledge is good with a total of 32 people (100,0%). For female students to further improve their knowledge about health, especially about ginger prebiotics to reduce menstrual pain, by practicing how to process them every month with herbs ABSTRAK Menurut WHO, didunia disminore angka kejadiannya cukup tinggi. Kejadian dismenorea pada perempuan muda rata-rata:16,8%-81%. Rata-rata di negara Eropa nyeri haid terjadi pada perempuan 45-97%. Prevelensi terendah Bulgaria 8,8%, tertinggi mencapai 94% dinegara Finlandia. Prevelensi dismenorea tertinggi sering ditemui pada remaja perempuan, yang diperkirakan: 20-90%. Sekitar 15% remaja mengalami dismenorea berat (Sulistyorinin, 2017). Tujuan penelitian ini untuk mengetahui Pengetahuan Mahasiswi tentang Prebiotik Jahe Untuk Penurunan Nyeri Haid di Mahasiswi DIII Kebidanan Universitas Ngudi Waluyo Ungaran Tahun 2021. Penelitian deskriptif kuantitatif dengan Survey. Sampel pada penelitian ini adalah mahasiswi DIII kebidanan Universitas Ngudi Waluyo Ungaran sejumlah 32 mahasiswi. Teknik pengambilan sampel dengan Sampling Total. Analisa data menggunakan distribusi frekuensi. Hasil penelitian ini kemudian diberi interpretasi berdasarkan variabel yang diteliti berdasarkan kriteria baik, cukup dan kurang. Hasil penelitian ini menunjukkan bahwa mahasiswi DIII kebidanan Universitas Ngudi Waluyo Ungaran memiliki pengetahuan tentang Prebiotik Jahe Untuk Penurunan Nyeri Haid, pengetahuan keseluruhan baik dengan jumlah 32 orang (100,0%). Bagi mahasiswi untuk lebih meningkatkan pengetahuannya tentang kesehatan khususnya tentang Prebiotik Jahe Untuk Penurunan Nyeri Haid yaitu dengan mempraktikkan cara pengolahannya setiap datang bulan dengan herbal.